A Preliminary Analysis of Oneota and Mississippian Serving Vessels at the Morton Village Site, West-Central Illinois. (July 2014) - Lieto, Joshua R.; O'Gorman, Jodie A.
The Morton Village Site (11-F-2) of west-central Illinois is an important site for understanding late prehistoric interactions between people of the Oneota and Mississippian traditions. Excavations at the site have uncovered ceramic vessels that appear to be inter-ethnic hybrids, combining Oneota decorative motifs with Mississippian forms. Primarily, this article examines metric and decorative motif variation of a sample of serving vessels and provides a preliminary data set that suggests avenues for further research that can be used to help better understand migrant Oneota adaptation to their new social environment. While the vessel forms have been previously noted, this is the first attempt to document their variability at Morton Village and establish their significance at the site.